2020
DOI: 10.3389/fonc.2020.578884
|View full text |Cite
|
Sign up to set email alerts
|

Time Difference of Arrival on Contrast-Enhanced Ultrasound in Distinguishing Benign Inflammation From Malignant Peripheral Pulmonary Lesions

Abstract: Introduction Worldwide, the incidence and mortality of lung cancer are at the highest levels, and the most lesions are located in the lung periphery. Despite extensive screening and diagnosis, the pathologic types of peripheral pulmonary lesions (PPLs) are difficult to diagnose by noninvasive examination. This study aimed to identify a novel index—time difference of arrival (TDOA)—to discriminate between benign inflammation and malignant PPLs. Methods Using contrast-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This significant difference between the two groups was consistent with the findings reported by Zhang et al, [ 29 ] Zhang, [ 10 ] and Tang. [ 30 ] The time required for the contrast agent to reach the lung lesion and adjacent lung tissue is affected by many factors, including heart function, lung disease, contrast agent injection speed, and other individual differences. The use of ∆AT as an observation index for the differential diagnosis of benign and malignant lung lesions can eliminate the influence of these factors and reduce the minor individual differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant difference between the two groups was consistent with the findings reported by Zhang et al, [ 29 ] Zhang, [ 10 ] and Tang. [ 30 ] The time required for the contrast agent to reach the lung lesion and adjacent lung tissue is affected by many factors, including heart function, lung disease, contrast agent injection speed, and other individual differences. The use of ∆AT as an observation index for the differential diagnosis of benign and malignant lung lesions can eliminate the influence of these factors and reduce the minor individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ∆AT as an observation index for the differential diagnosis of benign and malignant lung lesions can eliminate the influence of these factors and reduce the minor individual differences. Some studies [30][31][32] found that real-time comparative observations can be used to reduce the influence of individual differences, and the time difference between lesion and lung tissue enhancement (∆AT) can be used as an observation index for the differential diagnosis of benign and malignant lung lesions. ∆AT<2.5 seconds indicates benign lesions with early enhancement, while ∆AT>2.5 seconds indicates malignant lesions with late enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) adopts a blood pool contrast agent, which can be detected in microvessels with low flow, thus reducing Doppler artifacts to reflect the blood flow distribution more accurately ( 19 , 20 ). Like the liver, the lung also has a dual arterial blood supply, which may be helpful in the evaluation of peripheral pulmonary lesions ( 21 ). To date, CEUS has been widely used in the biopsy of various organs, including the lung, pancreas, and liver.…”
Section: Introductionmentioning
confidence: 99%
“…The use of contrast-enhanced ultrasound in conjunction with blood cell analysis improved the diagnostic accuracy of plasma cell mastitis (24). Min Tang demonstrated that CEUS has high diagnostic accuracy in distinguishing benign inflammation from the malignant peripheral pulmonary disease (25).…”
Section: Discussionmentioning
confidence: 99%